Estrutura genética de remanescentes de mangabeira no nordeste brasileiro - Amorim, Julie Anne Espíndola (2014)
Mangaba (Hancornia speciosa Gomes) is a native fruit tree and geographically widespread in the Northeast Region and the Cerrado of Brazil. Currently, the increasing degradation and consequent reduction of natural occurrence areas resulting from anthropogenic activities has been putting strong pressure on native populations of this species. The aim of this study was to evaluate the diversity and genetic structure of remaining populations of mangaba tree in Northeastern Brazil by means of microsatellite (SSR) markers. From 6 to 20 individuals per population were randomly sampled, totaling 94 individuals and six populations proceeding from the States of Sergipe (Reserva do Caju, Barra dos Coqueiros, and Abaís), Ceará (Jacarecoara and Tapera), and Pernambuco (Tamandaré). Microsatellite regions were amplified by using nine primers previously developed. All populations had positive inbreeding coefficients (f), indicating that they are endogamous populations, with excess of homozygotes, absence of random outcrossing and existence of factors influencing allelic randomness. The highest value of genetic variability was observed in the population Jacarecoara from the State of Ceará and the lowest value, in the population Barra dos Coqueiros from the State of Sergipe. The values of genetic diversity indices GST, RST, and FST estimated for the six populations were equal to 0.14 (p < 0.05), showing moderate genetic differentiation among them. The lowest value of FST pairs (p > 0.05) was found between the populations Jacarecoara and Tapera (0.005), while the highest value was observed between populations Barra dos Coqueiros and Jacarecoara (0.287). The population Jacarecoara was the most divergent in relation to the others. Bayesian clustering analysis showed genetic differentiation of H. speciosa populations in two groups (K = 2). Therefore, the results show that populations of H. speciosa have moderate interpopulational genetic diversity, with the greatest variation due to differences within populations (83.18%), and that these populations have genetic potential for in situ conservation of the species, as well as for germplasm collection for ex situ conservation.